A study on the strength of an armour-grade aluminum under high strain-rate loading - Appleby-Thomas, Gareth J.; Hazell, Paul J. (American Institute of Physics (AIP), 2010)
The aluminum alloy 5083 in tempers such as H32 and H131 is an established light- weight armour material. While its dynamic response under high strain-rates has been investigated elsewhere, little account of the effect of material orientation has been made. In addition, little information on its strength under such loadings is available in the literature. Here, both the longitudinal and lateral components of stress have been measured using embedded manganin stress gauges during plate-impact experiments on samples with the rolling direction aligned both orthogonal and parallel to the impact axis. The Hugoniot elastic limit, spall, and shear strengths were investigated for incident pressures in the range 1–8 GPa, providing an insight into the response of this alloy under shock loading. Further, the time dependence of lateral stress behind the shock front was investigated to give an indication of material response.
Keywords: impact; shock; aluminium armour; Hugoniot; strength